Ação terapêutica da dietilcarbamazina, albendazol e mebendazol em indivíduos microfilarêmicos por wuchereria bancrofti (Cobbold, 1877) - Lima, Ana Dalva Sampaio (2010)
Bancroftian filariasis is a disease caused by helminth nematodes of the Wuchereria bancrofti species. One of the strategies proposed by the WHO for elimination of disease has been the annual mass treatment with antifilarial drugs in areas with high prevalence. albendazole is recommended by the WHO to treat lymphatic filariasis, but nevertheless, studies are necessary to assess its actual microfilaricidal action. This study evaluated the reduction of microfilaremia and antigenemia in 201 microfilaremic patients by Wuchereria bancrofti, both males and females, living in the metropolitan area of Maceió-AL, diagnosed during haemoscopic surveys conducted in the general population of the city and treated with Citrate de diethylcarbamazine (DEC), albendazole and mebendazole in different strengths. The objective was to evaluate the parasitological cure of the patients and to show which of the drugs has the best efficacy in the treatment of bancroftose. The microfilaremic patients were divided into 6 groups: the first group received DEC at 6 mg / kg body weight / day, orally in a single intake / day, for 12 days (WHO recommended treatment). The second group received DEC at a dose of 6mg / kg of body weight / day, orally in one intake / day, for 6 days. The third group received DEC at a single dose of 6 mg / kg body weight + albendazole at a single oral dose of 400 mg / day. The fourth group received albendazole 400 mg oral dose (single dose) repeating this same treatment after two weeks. The fifth group received albendazole at a dose of 400 mg / day, orally in a single intake / day, for three days, repeating the treatment after two weeks. The sixth group received mebendazole at a dose of 100 mg twice daily orally for 3 days, repeating this treatment after two weeks. A portion of the patients in the first group and the second group were followed up for two years to check the reduction of microfilaraemia and antigenic over that time. All microfilariae patients completed the stages of the proposed therapeutic regimens and of these, 193 (96%) had microfilariaemia evaluated (puncture before treatment and after each treatment phase). Some of the microfilaremic individuals of the first and second groups still had microfilariaemia evaluated during the treatment. Of these 193 microfilaremic patients, 131 (68%) were male and 62 (32%) were female. The mean parasitemia before treatment regimens showed a reduction of 97.3% in the first group, 96.6% in the second group, 71.9% in the third group, 0% in the fourth group, 21, 3% in the fifth group, 29.5% in the sixth group. No statistically significant difference was observed in the reduction of mean microfilariaemia in the fourth, fifth and sixth groups (p> 0.05). The efficacy of the evaluated drugs was 40%, 36.1%, 12.5%, 0%, 3.0%, 3.7%, respectively. With the results obtained it can be concluded that diethylcarbamazine is effective as its microfilaricidal and also macrofilaricidal effect and remains the drug of choice for the treatment of bancroftian filariasis, the therapeutic scheme for 6 days being as effective in reducing microfilaremia as the regimen of 12 days recommended by WHO. albendazole and mebendazole in the schemes used do not have a microfilaricidal effect.